Factors Associated with Waste Management Behavior in Coastal Communities: Evidence from Binary Logistic Regression - Amanda Adityaningrum; Muhammad Rezky Friesta Payu; Bela Silfana (Jurusan Matematika FMIPA Universitas Pattimura, 2026)
Many communities continue to struggle with waste management, with improper handling still common, including in Gorontalo. To support effective waste management planning and intervention, it is crucial to identify factors influencing waste management behavior. The purpose of this study was to examine factors associated with waste management behavior using a binary logistic regression model. The study included 347 respondents in the South Leato Coastal Area, Dumbo Raya District, Gorontalo City, Gorontalo Province. It focused on attitude and waste management facilities as independent variables, as well as waste management behavior as a binary outcome. According to the likelihood ratio test, the logistic regression model was statistically significant (p-value < 0.05). As a result of the study, attitudes and waste management facilities were significantly associated with waste management behavior in the South Leato Coastal Area. People with a positive attitude were more likely to exhibit good waste management behavior than those with a negative attitude, and those with adequate waste management facilities were more likely to do so. Based on the Hosmer-Lemeshow test, the model fits the data well (p-value > 0.05).